93.5k views
0 votes
Place the following steps in order to complete the square and solve the quadratic equation, x^2 - 6x + 7 = 0.

Place the following steps in order to complete the square and solve the quadratic-example-1
User Senseiwa
by
5.9k points

2 Answers

3 votes

Answer:


x^2-6x=-7


x^2-6x+9=-7+9


(x-3)^2=2


√((x-3)^2)=\pm√(2)


(x-3)=\pm√(2)


x-3=3\pm√(2)

Explanation:

The given quadratic equation is


x^2-6x+7=0

Subtract 7 from both sides.


x^2-6x=-7 ...(1)

If an expression is
x^2+bx, then we add
((b)/(2))^2 to make it perfect square.


((b)/(2))^2=((-6)/(2))^2=9

Add 9 on both sides in equation (1).


x^2-6x+9=-7+9


(x-3)^2=2
[\because (a-b)^2=a^2-2ab+b^2]

Taking square root on both sides.


√((x-3)^2)=\pm√(2)


(x-3)=\pm√(2)

Add 3 on both sides.


x-3=3\pm√(2)

Therefore, the correct order is F, A, D, C, E and B.

User Ashmaroli
by
5.0k points
6 votes

Answer:

option f

option a

option d

option c

option e

option b

Explanation:

we have x^2 - 6x + 7 = 0

f) x^2 - 6x = -7

a) x^2 - 6x + 9 = -7+9

d) (x-3)^2=2

c)
\sqrt{(x-3)^(2)} = +-√(2)

e) x-3=+-
√(2)

b) x=3+-
√(2)

User Volna
by
6.6k points